Morphological and genetic identification of novel cryptic freshwater shrimp species (Caridina and Macrobrachium) in Northeastern Thailand using DNA barcoding - JUTHAPORN SAENGPRAJAK; EAKAPOL WANGKAHART; CHITCHOL PHALARAKSH; NOPPAKUN PAKDEENARONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Saengprajak J, Wangkahart E, Phalaraksh C, Pakdeenarong N. 2025. Morphological and genetic identification of novel cryptic freshwater shrimp species (Caridina and Macrobrachium) in Northeastern Thailand using DNA barcoding. Biodiversitas 26: 4886-4897. The phylogenetics clarifies species identities, reveals cryptic lineages, and assesses saline soils area may suppress cryptic diversity in freshwater prawns. Thus, this study used morphological identification and DNA barcoding to assess species composition and genetic variation of freshwater prawn species in saline and non-saline soil. Specimens were collected from 300 samples across 15 sites (saline-soil areas of Mahasarakham Province and non-saline habitats of Mukdahan Province) and identified based on morphology. Mitochondrial cytochrome C Oxidase I (COI) barcodes were also sequenced for molecular identification. Morphological analysis revealed three species (Macrobrachium lanchesteri, Macrobrachium niphanae, and Caridina macrophora) were found in both Mahasarakham and Mukdahan. In comparison, Caridina gracilirostris was recorded exclusively in Mukdahan, with four species (Macrobrachium lanchesteri, Macrobrachium niphanae, Caridina macrophora, and Caridina gracilirostris), with Mukdahan harboring one additional atyid (Caridina gracilirostris) not found in Mahasarakham. DNA barcoding revealed six distinct genetic lineages, including the four morphologically identified species and two cryptic lineages (Macrobrachium sp. and Caridina sp.) not detectable through morphology. Macrobrachium sintangense was identified by DNA in Mukdahan samples despite being misidentified morphologically. Mukdahan Province showed higher species richness and a lack of soil salinity, whereas saline conditions corresponded with lower diversity. Results demonstrated the effectiveness of DNA barcoding in revealing cryptic diversity and distributional differences influenced by environmental factors. Our findings provide a baseline for freshwater prawn conservation in Northeast Thailand and underscore the importance of integrative taxonomy for biodiversity assessment.